Racial differences in neuromyelitis optica spectrum disorder. (27th November 2018) - Kim, Su-Hyun; Mealy, Maureen A.; Levy, Michael; Schmidt, Felix; Ruprecht, Klemens; Paul, Friedemann; Ringelstein, Marius; Aktas, Orhan; Hartung, Hans-Peter; Asgari, Nasrin; Tsz-Ching, Jessica Li; Siritho, Sasitorn; et al.
Abstract : Objective: We aimed to evaluate racial differences in the clinical features of neuromyelitis optica spectrum disorder. Methods: This retrospective review included 603 patients (304 Asian, 207 Caucasian, and 92 Afro-American/Afro-European), who were seropositive for anti–aquaporin-4 antibody, from 6 centers in Denmark, Germany, South Korea, United Kingdom, United States, and Thailand. Results: Median disease duration at last follow-up was 8 years (range 0.3–38.4 years). Asian and Afro-American/Afro-European patients had a younger onset age than Caucasian patients (mean 36, 33, and 44 years, respectively; p < 0.001). During the disease course, Caucasian patients (23%) had a lower incidence of brain/brainstem involvement than Asian (42%) and Afro-American/Afro-European patients (38%) ( p < 0.001). Severe attacks (visual acuity ⩽0.1 in at least one eye or Expanded Disability Status Scale score ≥6.0 at nadir) at onset occurred more frequently in Afro-American/Afro-European (58%) than in Asian (46%) and Caucasian (38%) patients ( p = 0.005). In the multivariable analysis, older age at onset, higher number of attacks before and after immunosuppressive treatment, but not race, were independent predictors of severe motor disabilities at last follow-up. Conclusion: A review of a large international cohort revealed that race affected the clinical phenotype, age at onset, and severity of attacks, but the overall outcome was most dependent on early and effective immunosuppressive treatment.